2009
DOI: 10.2967/jnumed.108.055889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Matrix Metalloproteinase Expression in Atherosclerotic Plaques of Mice Deficient in Apolipoprotein E or Low-Density-Lipoprotein Receptor

Abstract: Matrix metalloproteinases (MMPs) are expressed in atherosclerotic plaques and play an important role in plaque instability. Methods: Using 99m Tc-labeled broad-spectrum MMP inhibitor (MPI), we performed noninvasive imaging of MMP expression with micro-SPECT/micro-CT in mice deficient in apolipoprotein E (ApoE 2/2 , n 5 14), mice deficient in low-density-lipoprotein receptor (LDLR 2/2 , n 5 14), and C57/BL6 mice as controls (n 5 7). Seven ApoE 2/2 and 7 LDLR 2/2 received a high-cholesterol diet. After in vivo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 35 publications
(48 reference statements)
1
47
0
2
Order By: Relevance
“…In vivo, future insights into the behavior of monocyte/macrophages will require a coordinated effort of technical and biological considerations. Although new technical approaches have been developed to track macrophages [62,82] and detect proteinase expression and activity in situ [66,69,86], a major technical challenge remains the intravital depth imaging limits that hinder resolution and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, future insights into the behavior of monocyte/macrophages will require a coordinated effort of technical and biological considerations. Although new technical approaches have been developed to track macrophages [62,82] and detect proteinase expression and activity in situ [66,69,86], a major technical challenge remains the intravital depth imaging limits that hinder resolution and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, future insights into the behavior of monocyte/macrophages will require a coordinated effort of technical and biological considerations. Although new technical approaches have been developed to track macrophages [62,82] and detect proteinase expression and activity in situ [66,69,86], a major technical challenge remains the intravital depth imaging limits that hinder resolution and sensitivity.In contrast to lymphocytes which use the protease-independent, amoeboid migration mode [1], macrophages use distinct migration modes, and, in situations where proteolytic activities are required, distinct proteases are used in different environments. Thus, although many questions remain, this research field is a key area whose results would potentially lead to the specific control of macrophage infiltration in determined tissue and the control of pathology.…”
mentioning
confidence: 99%
“…Importantly, we have found that this technique can successfully discriminate lipophilic compounds, in both intra-and extracellular regions, in a label-free manner. We have applied this method to study the structure and chemical makeup of plaques in two atherosclerotic mouse models: the LDL receptor-defi cient (LDLR Ϫ / Ϫ ) mouse and the ApoE-defi cient (ApoE Ϫ / Ϫ ) mouse (37)(38)(39)(40)(41). Our label-free imaging results reveal clusters of macrophage cells as well as needle-shaped and plate-shaped lipid crystal structures within plaque lesions.…”
mentioning
confidence: 99%
“…MMPs have therefore been considered ideal targets for molecular imaging of vulnerable plaque. In preclinical models of atherosclerosis, 123 I-or 125 I-labeled CGS 27023A, a broad-spectrum MMP inhibitor (32), and RP-805, a 99m Tc-labeled broad-spectrum MMP-inhibiting macrocyclic compound, have been shown to bind to atherosclerotic plaque (33,34).…”
Section: Matrix Remodeling By Mmpmentioning
confidence: 99%